Determinants of physical recreation among Generation Z people - Zawadka, Jan; Gabryjończyk, Piotr; Klata, Natalia (Turystyka i Rozwój Regionalny, 2024)
The aim of the study was to characterize the determinants of physical recreation undertaken by people from Generation Z. The research was conducted in 2024. The research sample consisted of 109 respondents. The study used a survey technique. The link to the questionnaire was posted on Facebook. The most frequently indicated source of inspiration for undertaking physical activity for the respondents were social media, as well as friends. The most frequently mentioned motives for practicing physical recreation included improving physical fitness, maintaining fitness and improving figure. The most frequently undertaken forms were walking, cycling and strength training. The respondents most often exercised in their own home, apartment or dormitory. The factor hindering more frequent physical activity was mainly lack of strength and fatigue, as well as insufficient free time.